Crisis, adjustment and economic policy in Latin America - David Ibarra (CEPAL Review, 1985)
The crisis in Latin America has a sui generis character, the elucidation of which has impelled the author to venture into virtually unexplored fields of in terdisciplinary analysis and to make generalizations covering a variety of national situations. Within this framework, he asserts that many of the central problems which look like conjunctural distortions—shortages of foreign exchange, deficits in public finance—in reality stem from imperfect structural adjustments both in the international economy and within the Latin American countries, the treatment and cure of which will be much more than a short-term matter.